Odpowiedzi

Najlepsza Odpowiedź!
2010-04-11T18:30:41+02:00
A)
3x +9y = 12 | :3
5x + 12y = 2

x + 3y = 4
5x + 12y = 2

x = 4 - 3y
5(4 - 3y) +12y = 2

20 - 15y + 12y = 2
- 3y = -18 | : (-3)
y = 6
x = -14

b)
3x + 2y = 2x + 6y + 3
4x + 1 = -5x - 7y +9

x - 4y = 3
9x + 7y = 8

x = 3 + 4y
9 (3 + 4y) + 7y = 8

27 + 36y + 7y = 8
43y = -19
y = -19/43
x = 3 - 76/43 = 1,23 (w przybliżeniu)

c)
3x - 2y + 3 = 2x
3x + 4y = 1

x - 2y = -3
3x + 4y = 1

x = 2y - 3
3 (2y - 3) + 4y = 1

6y - 9 + 4y = 1
10y = 10
y = 1
x = -1

d)
-2x + 5y = -3x + 4
3x - 2y = -5

x + 5y = 4
3x - 2y = -5

x = 4 - 5y
3 (4 - 5y) - 2y = -5

12 - 15y - 2y = -5
-17y = -17
y = 1
x = -1

_____________________
proszę o naj:)